2019
DOI: 10.1136/bmjgh-2019-001499
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pregnancy among young people in sub-Saharan Africa: a systematic review and narrative synthesis

Abstract: BackgroundSub-Saharan Africa has among the highest prevalence of teenage pregnancy in the world. Teenage mothers and their children are at risk to a host of medical, social and economic challenges. Adolescent pregnancy is a significant cost to the mother and newborn child, and also to their family and the wider society. Despite measures taken by some sub-Saharan nations to tackle the issue of adolescent pregnancy, the phenomenon remains a public health concern that is widespread throughout the region. Currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 66 publications
4
49
1
1
Order By: Relevance
“…The teenage pregnancy and childbearing situation in Malawi provide a compelling case to study. First, although teenage pregnancy has declined over the decade globally, Malawi has one of the highest rates [9–11] currently at 29% of the population. Secondly, although various programmes have been implemented to ensure that girls prevent early pregnancy, especially among the poor, over the decade[12,13], the impact of such programmes provides weak evidence of the determinants of teenage pregnancy, which undermines effectiveness, and thus leads to mixed outcomes in terms of teenage pregnancies and childbearing.…”
Section: Introductionmentioning
confidence: 99%
“…The teenage pregnancy and childbearing situation in Malawi provide a compelling case to study. First, although teenage pregnancy has declined over the decade globally, Malawi has one of the highest rates [9–11] currently at 29% of the population. Secondly, although various programmes have been implemented to ensure that girls prevent early pregnancy, especially among the poor, over the decade[12,13], the impact of such programmes provides weak evidence of the determinants of teenage pregnancy, which undermines effectiveness, and thus leads to mixed outcomes in terms of teenage pregnancies and childbearing.…”
Section: Introductionmentioning
confidence: 99%
“…This nding is re ective of studies conducted in sub-Saharan Africa and other parts of the world which investigated the predictors of pregnancy among young people: lack of SRH knowledge, parenting and family related attitudes as well as low parental communication and support were key predictors of unmet needs for contraception (21,25,26,27). A study from Uganda investigating healthcare perceptions of family planning among adolescents established that lack of community SRH knowledge, myths and misconceptions among adolescent girls and health care providers' attitudes were associated with non-use of contraceptives among adolescent girls (25).…”
Section: Discussionmentioning
confidence: 64%
“…This nding is re ective of studies conducted in sub-Saharan Africa and other parts of the world which investigated the predictors of pregnancy among young people: lack of sexual and reproductive health knowledge, parenting and family related attitudes as well as low parental communication and support were key predictors of unmet needs for contraception (21,25,26,27). A study from Uganda investigating healthcare perceptions of family planning among adolescents established that lack of community SRH knowledge, myths and misconceptions among adolescent girls and health care providers' attitudes were associated with non-use of contraceptives among adolescent girls (25).…”
Section: Discussionmentioning
confidence: 65%
“…The urgent need to encourage family and community discussions that dispel myths about contraceptive use cannot be overemphasized. Understanding parental and adolescents' contraceptive concerns and involving parents in adolescent pregnancy prevention programmes is vital as studies have shown that low parental communication and support is a key predictor of teenage pregnancies in sub-Saharan Africa (21). Whilst some parents have claimed that they have been engaged in sexuality education of their adolescents, in reality, such discussions are often barely communicated tacitly through intimation.…”
Section: Introductionmentioning
confidence: 99%